Twitter y el bienestar alimentario: Análisis de mensajes #slowfood reflejando el bienestar alimentario de consumidores - García-León, Ruth Areli (Departamento de Psicología y Comunicación de Texas A&M International University | Facultad de Trabajo Social y Desarrollo Humano de la Universidad Autónoma de Nuevo León, 2019)
This study examines how hashtag #SlowFood postings on social media site Twitter reflect the food well-being of consumers. 4102 tweets containing the hashtag #SlowFood were identified. Using interpretive content analysis, only 210 food-content messages in English language, from consumers were selected coded and interpreted. Displays of positive emotions and activities related with the slow food consumption on social media were found. By studying how consumers share their food well-being on social media, this research contributes to the understanding of food well-being and how it is practiced online.